2021
DOI: 10.1210/jendso/bvab048.545
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Encaleret (CLTX-305) on Mineral Physiology in Autosomal Dominant Hypocalcemia Type 1 (ADH1) Demonstrate Proof-of-Concept: Early Results From an Ongoing Phase 2b, Open-Label, Dose-Ranging Study

Abstract: Autosomal dominant hypocalcemia type 1 (ADH1) is a rare form of hypoparathyroidism caused by gain-of-function pathogenic variants in the gene (CASR) encoding the calcium-sensing receptor (CaSR). It is characterized by variable degrees of hypocalcemia, hyperphosphatemia, and hypomagnesemia, inappropriately low levels of parathyroid hormone (PTH) and hypercalciuria. Conventional therapy includes oral calcium and activated Vitamin D, targeting blood calcium at or slightly below the low-normal level to minimize hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…102,103 Preclinical and clinical studies have also indicated the potential utility of calcilytic drugs, which are CaSR negative allosteric modulators, as targeted therapies for ADH1. 100,[104][105][106] Patients with ADH1 may also exhibit ectopic calcification, and some develop a Bartter syndrome, characterized by renal salt wasting leading to volume depletion, hyper-reninaemic hyperaldosteronism, and hypokalaemic alkalosis. 61 Only a few kindreds with ADH2 have been reported and these patients have similar biochemical features to ADH1, although appear to have a milder urinary phenotype with less hypercalciuria.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…102,103 Preclinical and clinical studies have also indicated the potential utility of calcilytic drugs, which are CaSR negative allosteric modulators, as targeted therapies for ADH1. 100,[104][105][106] Patients with ADH1 may also exhibit ectopic calcification, and some develop a Bartter syndrome, characterized by renal salt wasting leading to volume depletion, hyper-reninaemic hyperaldosteronism, and hypokalaemic alkalosis. 61 Only a few kindreds with ADH2 have been reported and these patients have similar biochemical features to ADH1, although appear to have a milder urinary phenotype with less hypercalciuria.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Small clinical studies have reported that recombinant PTH is effective for treating symptomatic ADH1 patients without increasing urine calcium excretion 102,103 . Preclinical and clinical studies have also indicated the potential utility of calcilytic drugs, which are CaSR negative allosteric modulators, as targeted therapies for ADH1 100,104–106 . Patients with ADH1 may also exhibit ectopic calcification, and some develop a Bartter syndrome, characterized by renal salt wasting leading to volume depletion, hyper‐reninaemic hyperaldosteronism, and hypokalaemic alkalosis 61 .…”
Section: Hereditary Hypocalcaemic Disordersmentioning
confidence: 99%
“…(143) The calcilytic encaleret was recently shown to normalize serum calcium, phosphorus, and magnesium as well as urine calcium in an early Phase 2 study. (144) Knowledge Gaps and Future Research Directions…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…Urinary calcium excretion, which was elevated at baseline, became normal in three patients and undetectable in three while on encaleret. ( 95 )…”
Section: Emerging Therapies For Hypoptmentioning
confidence: 99%
“…Urinary calcium excretion, which was elevated at baseline, became normal in three patients and undetectable in three while on encaleret. (95) Patient Perspective Members of The HypoPARAthyroidism Association, Inc. believe that a single treatment strategy may not be ideal for all patients. Each patient with HypoPT has different symptoms and complications.…”
Section: Emerging Therapies For Hypoptmentioning
confidence: 99%